2017
DOI: 10.1186/s12890-017-0508-1
|View full text |Cite
|
Sign up to set email alerts
|

Fever after bronchoscopy: serum procalcitonin enables early diagnosis of post-interventional bacterial infection

Abstract: BackgroundThe aim of this study was to differentiate unspecific and self-limiting fever after bronchoscopy from fever due to infection by using serum procalcitonin, C-reactive protein and neutrophil count. Furthermore, frequency of fever after bronchoscopy and procedures as possible risk factors were evaluated.MethodsThree hundred and fourteen consecutive patients were included. All bronchoscopies were performed using jet-ventilation and general anesthesia. Patients were analyzed according to interventions per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…A bronchoscopy is an adequate technique for physicians and scientists to obtain airway cells (e.g., bronchial brushings) or tissues from a patient’s lower airway to diagnose diseases and perform basic and translational research. However, there are risks following a bronchoscopy including bronchial spasms, bleeding and infection [ 1 ]. A minimally invasive approach such as nasal brushings is urgently needed to study lower airway diseases such as asthma.…”
Section: Introductionmentioning
confidence: 99%
“…A bronchoscopy is an adequate technique for physicians and scientists to obtain airway cells (e.g., bronchial brushings) or tissues from a patient’s lower airway to diagnose diseases and perform basic and translational research. However, there are risks following a bronchoscopy including bronchial spasms, bleeding and infection [ 1 ]. A minimally invasive approach such as nasal brushings is urgently needed to study lower airway diseases such as asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Fever after bronchoscopy, especially bronchoalveolar lavage (BAL) suggested by several authors may initiate by an endogenous immune response. A systemic in ammatory response is characterized by an increase in circulating cytokine levels such as tumor necrosis factor (TNF)-alpha, interleukin (IL)-1 beta, and IL-6 [9][10][11][12]. During polypectomy, adenomatous polyps have an in ammatory stromal microenvironment, rich in macrophages, neutrophils, and T helper cells [13] that can be a trigger for endogenous immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Fever is a common complication after bronchoscopy, and the related literature reports that the incidence is about 10–20% [ 4 6 ]. Further studies showed that fever incidence rates after bronchoscopy in elderly people over 80 years old and those under 80 years old were 7.6% and 4.1%, respectively, and there was no statistically significant difference between them [ 7 ].…”
Section: Discussionmentioning
confidence: 99%